THE PORTRAYAL OF INDIVIDUAL DIFFERENCES IN A PICTURE BOOK CLEO AND CLOE'S COLOURFUL DAY : A VERBAL AND VISUAL ANALYSIS - Permatasari, Putri (2014)
The present study entitled The Portrayal of Individual Differences in A Picture Book "Cleo and Cloe's Colourful Day":A Verbal and Visual Analysis investigates the verbal and visual portrayal of individual differences in the picture book revealed in the twin sisters. The study empoys a descriptive qualitative method to describe and interpret the data. Some theoretical frameworks were applied in this present study. In terms of verbal analyisis, transitivity proposed by Halliday (2002) was applied and for visual analysis, this study employed Kress and van Leuween's (2006) visual grammar as well as Joyce and Gaudin's (2011) picture book's analysis. Furthermore, the last theoretical framework is individual differences characteristics from Jimoh and Olawuyi (2008). The analysis of verbal texts demonstrate that individual differences of the twin sisters in the picture book are mostly presented through material process. It implies that the author wants to show the twin sisters's individual differences from the activity they choose and how they do that. Meanwhile, all visual elements covered in three metafunctions (representational, interpretational and compositional metafunction) also play a role in revealing the individual differences of the twin sisters in the picture book. The findings indicate that both verbal and visual elements in the picture book match each other in portraying the individual differences.